An electroactive oligo-EDOT platform for neural tissue engineering - Ritzau-Reid,K; Spicer,C; Gelmi,A; Grigsby,CL; Ponder,Jr J; Bemmer,V; Creamer,A; Vilar,R; Serio,A; Stevens,M (Advanced Functional Materials, 2020)
The unique electrochemical properties of the conductive polymer poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) make it an attractive material for use in neural tissue engineering applications. However, inadequate mechanical properties, and difficulties in processing and lack of biodegradability have hindered progress in this field. Here, we have improved the functionality of PEDOT:PSS for neural tissue engineering by incorporating 3,4-ethylenedioxythiophene (EDOT) oligomers, synthesised using a novel end-capping strategy, into block co-polymers. By exploiting end-functionalised oligoEDOT constructs as macroinitiators for the polymerization of poly(caprolactone) (PCL), we produce a block co-polymer that is electroactive, processable, and bio-compatible. By combining these properties, we were able to produce electroactive fibrous mats for neuronal culture via solution electrospinning and melt electrospinning writing (MEW). Importantly, we also show that neurite length and branching of neural stem cells can be enhanced on our materials under electrical stimulation, demonstrating the promise of these scaffolds for neural tissue engineering.